Human flourishing for wellbeing in society, communities and organizations: A case study in Bangladesh - Koli, Kamrunnahar (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Human flourishing refers to the holistic growth of individuals in terms of physical and mental well-being, influenced by globalization and technological advancements. It involves adapting to diverse demands, marketplaces, and environmental fluctuations. The study analyzes the relationship between engagement in arts and humanities and human well- being in Bangladesh, focusing on enhancing it for society, community, and organization. Quantitative analysis is used to analyze key aspects of human well-being across various sectors.